2022
DOI: 10.1177/08903344221081840
|View full text |Cite
|
Sign up to set email alerts
|

Rooming-In Practice During the Pandemic: Results From a Retrospective Cohort Study

Abstract: Background: The Coronavirus disease 2019 (COVID-19) pandemic emerged in December 2019 and spread rapidly worldwide. So far, evidence regarding the breastfeeding and rooming-in management of mothers with COVID-19 and their newborn infants is scarce. Research Aims: 1) To assess the rate of exclusive breastfeeding at discharge among mothers with COVID-19 and their newborn infants managed either using a rooming-in or a separation regimen; and 2) to evaluate different neonatal outcomes, including the need for re-ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Investigators of an Italian study compared breastfeeding rates of women with COVID-19 according to whether rooming-in or separation of mother and neonate was practiced. Consistent with our results, rooming-in was associated with a significantly higher breastfeeding rate (Costa et al, 2022). In the INTERCOVID study, feeding an infant with their mother’s own milk was shown not to increase the transmission of COVID-19 when adequate hygienic precautions were taken (Raschetti et al, 2020; Villar et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…Investigators of an Italian study compared breastfeeding rates of women with COVID-19 according to whether rooming-in or separation of mother and neonate was practiced. Consistent with our results, rooming-in was associated with a significantly higher breastfeeding rate (Costa et al, 2022). In the INTERCOVID study, feeding an infant with their mother’s own milk was shown not to increase the transmission of COVID-19 when adequate hygienic precautions were taken (Raschetti et al, 2020; Villar et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…7 Before the Omicron surge, in our hospital, mother with COVID-19-neonate dyads were discharged not earlier than 72 hours, following the previous standard protocol. 8 However, to face the overload of the postpartum ward due to the omicron surge, FPG established a new policy, determining ED of mothers with COVID-19 and their newborns, and setting up a postdischarge clinic dedicated to the follow-up of ED newborns.…”
mentioning
confidence: 99%